PERAN KREDIBILITAS INFLUENCER PADA HUBUNGAN ANTARA OVER ENDORSEMENT DAN NIAT BELI - Fukuhara, Jennifer Angelyn; Wiryakusuma, I Gusti Bagus Yosia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to investigate the effect of Over Endorsement on Purchase Intentions through the mediating role of Influencer Credibility and the moderating role of Product Interest. The research was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with a sample of 207 respondents consisting of active social media users. The results reveal several key findings: (1) Over Endorsement does not significantly influence Influencer Credibility, (2) Influencer Credibility has a significant positive effect on Purchase Intentions, (3) Product Interest does not moderate the relationship between Over Endorsement and Influencer Credibility, and (4) Influencer Credibility does not mediate the relationship between Over Endorsement and Purchase Intentions. These findings suggest that while influencer credibility is an essential factor in driving purchase intentions, the phenomenon of over endorsement does not necessarily reduce or enhance influencer credibility, nor does it indirectly affect purchase behavior. This research contributes to the understanding of influencer marketing dynamics by highlighting the importance of credibility in shaping consumer decision-making, while also addressing the limited role of over endorsement in influencing consumer perceptions and behaviors.